THE RESPIRATORY HEALTH HAZARDS OF VOLCANIC ASH: A REVIEW FOR VOLCANIC RISK MITIGATION - Horwell C.J.; Baxter P.J. (My University, 2006)
Studies of the respiratory health effects of different types of volcanic ash have been undertaken only in the last 40 years, and mostly since the eruption of Mt. St. Helens in 1980. This review of all published clinical, epidemiological and toxicological studies, and other work known to the authors up to and including 2005, highlights the sparseness of studies on acute health effects after eruptions and the complexity of evaluating the long-term health risk (silicosis, non-specific pneumoconiosis and chronic obstructive pulmonary disease) in populations from prolonged exposure to ash due to persistent eruptive activity. The acute and chronic health effects of volcanic ash depend upon particle size (particularly the proportion of respirable-sized material), mineralogical composition (including the crystalline silica content) and the physico-chemical properties of the surfaces of the ash particles, all of which vary between volcanoes and even eruptions of the same volcano, but adequate information on these key characteristics is not reported for most eruptions. The incidence of acute respiratory symptoms (e.g. asthma, bronchitis) varies greatly after ashfalls, from very few, if any, reported cases to population outbreaks of asthma. The studies are inadequate for excluding increases in acute respiratory mortality after eruptions. Individuals with pre-existing lung disease, including asthma, can be at increased risk of their symptoms being exacerbated after falls of fine ash. A comprehensive risk assessment, including toxicological studies, to determine the long-term risk of silicosis from chronic exposure to volcanic ash, has been undertaken only in the eruptions of Mt. St. Helens (1980), USA, and Soufrière Hills, Montserrat (1995 onwards). In the Soufriére Hills eruption, a long-term silicosis hazard has been identified and sufficient exposure and toxicological information obtained to make a probabilistic risk assessment for the development of silicosis in outdoor workers and the general population. A more systematic approach to multi-disciplinary studies in future eruptions is recommended, including establishing an archive of ash samples and a website containing health advice for the public, together with scientific and medical study guidelines for volcanologists and health-care workers. © Springer-Verlag 2006.
Keywords: HAZARD; HEALTH; RESPIRATORY; REVIEW; RISK MITIGATION; VOLCANIC ASH